CARACTERIZAÇÃO E AVALIAÇÃO DA QUALIDADE DOS CIGARROS CONTRABANDEADOS NO BRASIL - Silva, Cleber Pinto da (2015)
One in four cigarettes consumed by the population in Brazil comes from smuggling, which are not monitored and may increase the risk the health of those who consume them. In this study, determinations were performed by Atomic Absorption Spectroscopy (FAAS), copper (Cu), manganese (Mn), zinc (Zn), cobalt (Co), chromium (Cr), cadmium (Cd), lead (Pb) , iron (Fe) and nickel (Ni), Atomic Absorption Spectrometry with Graphite Furnace (GFAAS) for arsenic (As) in thirty brands of cigarettes smuggled more in Brazil. In addition, those elements were analyzed in two tobacco hybrid varieties with soil and fertilizer in the pretense of obtaining differences of absorption of these elements during the 90-day culture period. An additional study was conducted to characterize the thirty contraband cigarette brands by gravimetric measurements in soils of pH and pH tobacco smoke from the side. The results show that 65% of smuggled cigarette brands have high concentrations of toxic elements, with values of up to eleven times higher than for Cr, Ni, Cd and Pb found in cigarettes legalized in Brazil. It was observed that 46.6% of the marks were twice the average concentration As described in a Brazilian authenticated cigarettes. The results showed that Cr, Ni, Pb and As accumulate at higher concentrations in tobacco roots. No significant differences were determined using the U test in the concentrations of these elements between the two varieties over the course of cultivation. For quality testing, 50% of the brands had high moisture content, 96% had high levels of ash and 90% have pH alkaline smoke. In soil tests 81.2% of the brands had some type of contaminant types of fungi, insect fragments, grass and mites above rated as good hygiene practices by ANVISA. These characteristics point to contamination by toxic elements through poor hygiene practices, which may contribute to tobacco contamination by chemical and biological agents. Thus, the consumption of this type of cigarette, which do not have the least control, can increase the risks to health of those who consume them.